Investigations on behavioral characteristics of asphalt binder with crumb rubber modification: Rheological and thermo-chemical approach. (30th August 2018) - Venudharan, Veena; Biligiri, Krishna Prapoorna; Das, Narayan Chandra
Highlights: Performed thermo-chemical analyses of asphalt binders covering 5000 data points. Assessed AR binders with varying crumb rubber gradations and dosages. CR inclusions augmented AR binders' thermal stability corroborated by TGA. Increased intensity of sulfoxide in AR confirmed binders' enhanced performance. Framed guidelines to choose outstanding AR binder based on parametric relationships. Abstract: The objective was to investigate the rheological and thermo-chemical behavior of asphalt-rubber (AR) binders and to evaluate the effect of various parameters on AR binder performance. The effort encompassed binder consistency, rheological, thermogravimetric, and Fourier transform infrared spectroscopy analyses of twelve different asphalts. It was found that CR inclusions not only improved the physical characteristics but also influenced the chemical and thermal properties of asphalt binder. Furthermore, it was inferred that employing higher CR dosages and fine CR gradations in asphalt binder will aid in producing an outstanding AR binder capable of performing well under extreme traffic and environmental conditions.